Mengukur Kesiapan Etika Digital Dalam Analisis Persepsi Multidisiplin Mahasiswa Universitas Negeri Medan Terhadap Pancasila Sebagai Dasar Nilai Pengembangan Ilmu (DPI) Dalam Menghadapi Disrupsi Teknologi - Manalu, Syuratty Astuti Rahayu; Nainggolan, Yesi Rama Indah; Nasution, Nur Hidayati; Pandiangan, Betrand Samuel; Tarigan, Peter Teguh; Silalahi, Ritayana; Sarumaha, Elisabeth S. Putri (Sagita Academia Journal, 2025)
This study aims to measure the readiness and analyze the perceptions of Universitas Negeri Medan (UNIMED) students across various faculties regarding the implementation of Pancasila as the Basis for scientific development values (DPI) within digital ethics practices. The core problem addressed is the gap between the ideological recognition of Pancasila and the reality of behavior in cyberspace, which is susceptible to technological disruption and moral crises. A descriptive qualitative method, utilizing in-depth interviews across different faculties at UNIMED, was employed to identify the convergence and conflict of values in technology use. The research results consistently indicate that students acknowledge the urgency of Pancasila as a "moral compass" and "cultural filter", specifically highlighting the Second Sila (Just and Civilized Humanity) and Fourth Sila (Guided by Wisdom) as primary countermeasures against cyberbullying and hoax. However, a significant implementation gap (value lag) was identified, primarily driven by cultural factors such as pragmatism and the instant culture prevalent in social media. Specifically, students perceive the Fifth Sila (Social Justice) as the most challenging value to realize in online interactions due to the influence of algorithmic bias and lack of context. These findings emphasize the necessity for a reorientation of the DPI curriculum towards a more applicative and preventive approach, and the integration of transcendental ethics into technology design.